Expanding public debate? Examining the impact of India's top English language political talk shows. Issue 2 (3rd April 2023) - Bhat, Prashanth; Chadha, Kalyani
Abstract: As a genre, current affairs talk shows occupy a distinct space within the Indian television universe. Typically built around a single host and invited guests, talk shows constitute a relatively inexpensive format that most news channels deploy to market themselves. Although the extent to which such shows enhance the potential of rational-critical debate has been widely investigated in Western contexts, their implication for public deliberation remains unclear, at least in the case of India. Through an ethnographic content analysis (ECA) of such shows as represented by Newshour aired on Times Now and The Debate aired on Republic TV, this article explores the presentation styles adopted by these programs and their content both in terms of the participants invited and the range of topics discussed. This research found that instead of enabling meaningful deliberation on a variety of important civic issues, television talk shows in India were fixated on promoting religious majoritarianism, defending the policies of the Modi government, and advocating hyper-nationalism. Further, employing a combative style and polarizing tone, talk show hosts were found to stifle dissenting voices and forestall free expression. Ramifications of such blatant partisanship among current affairs talk shows for the Indian public sphere are discussed.